Pemikiran Gusdur dalam Buku Islam Kosmopolitan dan Pendidikan Demokrasi - Humaedi (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2017)
Democratic civic education for Indonesian people has been carried out in various forms. During Soekarno's old order, democratic education was published on the concept of